PENGARUH GAYA KEPEMIMPINAN, KESEHATAN KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP TINGKAT SEMANGAT KERJA PADA KARYAWAN PT. MASTER CASH AND KREDIT RANTAU PRAPAT KABUPATEN LABUHANBATU - Ramadani, Kurnia (Universitas Labuhanbatu, 2021)
PT Master cash and credit which is located on Jln.SM.Raja Simpang Mangga in carrying out its activities requires a lot of factors and factors encourage a job so that the work can be done well with enthusiasm and goals that will be realized and carried out properly such as This is because the company needs a good leadership style and the work health of every employee and work discipline so that all are properly directed and comply with the rules that exist in the company and the work environment which greatly affects every company and good working morale. The purpose of this study was to determine the effect of leadership style, occupational health, work discipline and work environment on the level of morale of employees of PT. Master cash and credit Rantauprapat using quantitative methods by distributing questionnaire data with a population of 40 people. The analysis technique used is Multiple Linear Regression with a significance level of 5%. The results of the study using Multiple Linear Regression Analysis obtained a regression equation Y = 14.401 + 0.323X1 + 0.217X2 + 0.234X3 + 0.308X4, meaning that there is a positive and significant influence on Leadership Style, Occupational Health, Work Discipline and Work Environment on the Level of Morale. The simultaneous influence of Leadership Style, Occupational Health, Work Discipline and Work Environment on Work Morale Level with a significance value of 0.001 Work Spirit (Y) is influenced by the Variables of Leadership Style, Occupational Health, Work Discipline and Work Environment on Work Spirit Level of 34.4 %. While the remaining 65.6% is influenced by other factors.